NGHIÊN CỨU CHẾ TẠO VÀ TÍNH CHẤT HẠT NANO HỢP KIM RỖNG MPt (M=Co VÀ Fe) CHO ĐỊNH HƯỚNG ỨNG DỤNG TRONG PIN NHIÊN LIỆU - Cừ, Nguyễn Mậu; Chính, Nguyễn Quang; Lư, Lê Trọng; Dung, Ngô Thanh; Hải, Trần Đắc; Thành, Ngô Bá; Thái, Vũ Quốc (Vietnam Journal of Science and Technology, 2014)
Hollow alloy nanomaterials have been extensively studied in the recent years, especially in the fields of catalysis and biomedicine due to their advanced properties. In the fuel cell applications, hollow alloy nanomaterials formed between transition metals such as Co, Fe or Ni and Pt have attracted a great interest as effective catalysts for their low cost, high catalytic activity and performance stability. In this paper, we present a facile synthetic method for the preparation of CoPt and FePt hollow alloy nanoparticles with controllable size. Here, the particle size (perimeter size) could be tuned from 17 đến 70 nm by changing the length and concentration of polymer. The obtained nanoparticles have been characterised by Transmission electron microscope (TEM), X-ray diffraction (XRD) and Energy dispersive X-ray spectroscopy (EDS).